2015
DOI: 10.1021/acschembio.5b00779
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantification of Ribosome Inhibition by Aminoglycoside Antibiotics in Living Bacteria Using an Orthogonal Ribosome-Controlled Fluorescent Reporter

Abstract: The ribosome is the quintessential antibacterial drug target, with many structurally and mechanistically distinct classes of antibacterial agents acting by inhibiting ribosome function. Detecting and quantifying ribosome inhibition by small molecules and investigating their binding modes and mechanisms of action are critical to antibacterial drug discovery and development efforts. To develop a ribosome inhibition assay that is operationally simple, yet provides direct infonnation on drug target and mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Other ensemble in vitro kinetics experiments, following tripeptide formation using native E. coli tRNAs ( 11 ), show slow but significant translocation in the presence of all three drugs, with a reduction in translocation rate somewhere in between those of the in vitro single-molecule experiments ( 11 , 21 ) and the in vitro ensemble experiments ( 20 ). Finally, previous indirect reporter-based in vivo results ( 44 ) also suggest only partial inhibition of translation in the presence of the three aminoglycoside drugs in question at similar concentrations, with apramycin giving the weakest response, in line with our findings ( Fig. 5 ).…”
Section: Discussionsupporting
confidence: 92%
“…Other ensemble in vitro kinetics experiments, following tripeptide formation using native E. coli tRNAs ( 11 ), show slow but significant translocation in the presence of all three drugs, with a reduction in translocation rate somewhere in between those of the in vitro single-molecule experiments ( 11 , 21 ) and the in vitro ensemble experiments ( 20 ). Finally, previous indirect reporter-based in vivo results ( 44 ) also suggest only partial inhibition of translation in the presence of the three aminoglycoside drugs in question at similar concentrations, with apramycin giving the weakest response, in line with our findings ( Fig. 5 ).…”
Section: Discussionsupporting
confidence: 92%
“…30 Dr. Chad M. Novince et al have reported that antibiotics can destroy a healthy intestinal microbiome, induce a pro-inflammatory reaction, increase osteoclast activity, and affect bone development after puberty. 31 So far, the detection of antibiotics principally covers liquid chromatography-tandem mass spectrometry, 32,33 optical spectrometry, 34,35 capillary electrophoresis, 36 and ion mobility spectrometry. 37 However, due to deficiencies such as high cost, complicated manipulations, and being timeintensive, these methods are usually limited in practical application.…”
Section: Introductionmentioning
confidence: 99%
“…Superimposed structures of 4,6-disubstituted and 4,5-disubstituted 2-deoxystreptamine AGs in complex with A-site rRNA nucleotides indicated that rings I and II of these antibiotics (Figure ) occupy an almost identical space in the binding site. These superimposed AG structures also indicate that the ribofuranose ring III of the 4,5-disubstituted 2-deoxystreptamine subfamily and ring III of the 4,6-disubstituted 2-deoxystreptamine subfamily occupy different spaces. …”
Section: Introductionmentioning
confidence: 86%